Changes in clinical indications for community antibiotic prescribing for children in the UK from 1996 to 2006: will the new NICE prescribing guidance on upper respiratory tract infections just be ignored?. Issue 5 (9th December 2008) - Thompson, P L; Spyridis, N; Sharland, M; Gilbert, R E; Saxena, S; Long, P F; Johnson, A P; Wong, I C K
Abstract : Objective: To analyse changes in clinical indications for community antibiotic prescribing for children in the UK between 1996 and 2006 and relate these findings to the new NICE guidelines for the treatment of upper respiratory tract infections in children. Study design: Retrospective cohort study. Method: The IMS Health Mediplus database was used to obtain annual antibiotic prescribing rates and associated clinical indications in 0–18-year-old patients between 1 January 1996 and 31 December 2006 in the UK. Results: Antibiotic prescribing declined by 24% between 1996 and 2000 but increased again by 10% during 2003–2006. Respiratory tract infection was the most common indication for which an antibiotic was prescribed, followed by "abnormal signs and symptoms", ear and skin infections. Antibiotic prescriptions for respiratory tract infections have decreased by 31% (p<0.01) mainly because of reduced prescribing for lower respiratory tract infections (56% decline, p<0.001) and specific upper respiratory tract infections including tonsillitis/pharyngitis (48% decline, p<0.001) and otitis (46% decline, p<0.001). Prescribing for non-specific upper respiratory tract infection increased fourfold (p<0.001). Prescribing for "abnormal signs and symptoms" increased significantly since 2001 (40% increase, p<0.001). Conclusion: There has been a marked decrease in community antibiotic prescribing linked to lower respiratory tract infection, tonsillitis, pharyngitis and otitis. Overall prescribing is now increasing again but is associated with non-specific upper respiratory tract infection diagnoses. General practitioners may be avoiding using diagnoses where formal guidance suggests antibiotic prescribing is not indicated. The new NICE guidance on upper respiratory tract infections is at risk of being ignored.